2022
DOI: 10.3390/app12189012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Different Core Topologies in Sandwich-Structured Composites Subjected to Air-Blast Impact

Abstract: Air-blast loading is a serious threat to military and civil vehicles, buildings, containers, and cargo. Applications of sandwich-structured composites have attracted increasing interest in modern lightweight design and in the construction of dynamic loading regimes due to their high resistance against blast and ballistic impacts. The functional properties of such composites are determined by the interplay of their face sheet material and the employed core topology. The core topology is the most important param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…However, the employed CONWEP framework which is already based on experimental investigation partially fills this gap. A similar approach was used by Walkowiak et al [28] where they investigated different core topologies in sandwich panels subjected to air blast loading. However, the distinguishing feature of the present study is the analysis of different loading regimes in terms of in-plane and axial loading directions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the employed CONWEP framework which is already based on experimental investigation partially fills this gap. A similar approach was used by Walkowiak et al [28] where they investigated different core topologies in sandwich panels subjected to air blast loading. However, the distinguishing feature of the present study is the analysis of different loading regimes in terms of in-plane and axial loading directions.…”
Section: Introductionmentioning
confidence: 99%
“…Osička et al [8] measured the cutting force during the machining of hardened steel with cubic boron nitride tools. By means of the finite element code ABAQUS/Explicit, Walkowiak et al [9] presented a numerical study of the structural behavior of prismatic and lattice core topologies in sandwich-structured composites subjected to air-blast impact. Danfá et al [10] experimentally showed that powder TiO 2 impregnated in a ceramic material can improve liquid wastewater treatment via the photocatalysis process.…”
mentioning
confidence: 99%